A bibliometric analysis of publications on venous thromboembolism in children from 1988 to 2019. Issue 20 (15th May 2020) - Tian, Lingyun; Zhang, Ying; Zeng, Jiaqi; Wang, Liqian; Gao, Huimin; Su, Yanan; Li, Yinglan
Abstract: Introduction: Venous thromboembolism (VTE) in children not only imposes a heavy burden on the medical resources and economy of the society, but also seriously affects the growth and development of children, even threaten children's lives. A large number of publications have been performed in this field in recent years. In this bibliometric analysis, publications on VTE in children were examined and analyzed to explain the present research hotspots. Methods: Articles related to VTE in children published in the PubMed database from 1988 to June 18, 2019 were selected as the research sample. BICOMB software was used to retrieve the annual publications, journals, journal source countries and the high-frequency major medical subject headings (MeSH) terms on the articles. Then, the co-word matrix was constructed by BICOMB using the selected high-frequency MeSH terms. Next, gCLUTO software was used to analyze the matrix by double clustering and visual analysis in a strategy of hotspot identification. In addition, CiteSpace software was used to perform the knowledge map of co-authors to explore the core authors. Results: One thousand seven hundred seventy-nine articles on VTE in children were obtained. Seven hundred ninety academic journals distributed in 58 countries have published articles on VTE in children, and the developed countries and the United States were the major force in the journal source countries. Nowak-Göttl U occupied an important position in this field. We constructed a co-word matrix composing of 37 high-frequency MeSH terms, generated visual matrix and visual hill, and classified the hot-spots into 5 aspects based on 8 categories. Conclusion: The results show that the research trend of children's VTE has been increasing gradually, and the sound achievement has been obtained in these hotspots in relation to the area of inherited thrombophilia, prevention and control, treatment, diagnosis, prevalence, risk factors, and complication study. However, there is a lack of communication and cooperation in this field, and the gap of national and regional research results is huge. To sum up, this study provides evidence and guidance for researchers, clinicians, and educators.